2022
DOI: 10.1038/s41598-022-20439-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and anatomical characterization of yellow diploid potato flower for effective breeding program

Abstract: The diploid yellow potato (Solanum tuberosum L. Phureja Group) is an important plant genetic resource. In this study, we report for the first time the characterization of anther development and pollen formation in the cultivar Criolla Colombia. The description of morphological and histological characters of buds and flowers at different developmental stages permitted to identify ten main stages, from the differentiation of the male cells of the sporangium, meiosis, microspores formation and maturation, to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…It was similarly reported that the process of microspore formation and meiosis in strawberry was mainly concentrated 18–14 days before flowering (bud length was 1–3 mm) [ 55 ]. In addition, in diploid yellow potato ( Solanum tuberosum L. Phureja Group), the meiosis was completed when the bud length was 7.5–8.9 mm [ 56 ]. Therefore, in this study, higher expression levels of restorer genes can be detected in the early stage of bud formation.…”
Section: Discussionmentioning
confidence: 99%
“…It was similarly reported that the process of microspore formation and meiosis in strawberry was mainly concentrated 18–14 days before flowering (bud length was 1–3 mm) [ 55 ]. In addition, in diploid yellow potato ( Solanum tuberosum L. Phureja Group), the meiosis was completed when the bud length was 7.5–8.9 mm [ 56 ]. Therefore, in this study, higher expression levels of restorer genes can be detected in the early stage of bud formation.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more challenging from a breeding perspective are reproductive problems such as male (or female) sterility associated with cytoplasm types and specific nuclear genes [ 170 ]. Diploid potato landraces (e.g., S. tuberosum Phureja group) and their wild relatives are not yet as well-characterized reproductively as in other major crops (see for example, [ 171 ]), offering enormous potential for better understanding the remaining conundrums of potato reproductive biology and their exploitation in biotechnological applications. Future analyses and studies focusing on evaluating the molecular basis of this dosage system, and its probable links to genomic imprinting mechanisms, will pave the way to overcoming breeding barriers in potato improvement caused by endosperm malfunction and aberrant seed development.…”
Section: Breeding Strategies and Challenges To Using Apomixis In Potatomentioning
confidence: 99%